An Organocatalytic Regiospecific Synthesis of 1, 5‐Disubstituted 4‐Thio‐1, 2, 3‐triazoles and 1, 5‐Disubstituted 1, 2, 3‐Triazoles. Issue 47 (7th October 2015) - Ramachary, Dhevalapally B.; Krishna, Patoju M.; Gujral, Jagjeet; Reddy, G. Surendra
Abstract: Organocatalytic azide–ketone [3+2] cycloaddition (OrgAKC) of a variety of 1‐aryl‐2‐(arylthio)ethanones and 1‐alkyl‐2‐(alkylthio)ethanones with different aryl or alkyl azides is reported in dimethyl sulfoxide or solvent‐free under ambient conditions to furnish 1, 5‐disubstituted 4‐thio‐1, 2, 3‐triazoles in a regiospecific manner, which are further converted into useful 1, 5‐disubstituted 1, 2, 3‐triazoles by treatment with Raney Ni at 25 °C for 1–3 h. Notable features of the OrgAKC reaction include high rate and selectivity, solvent‐free conditions, easily available substrates and catalysts, a wide range of synthetic and medicinal applications, and excellent yields generating a vast library of triazoles. Abstract : Organo‐click : Organocatalytic azide–ketone [3+2] cycloaddition (OrgAKC) of a variety of 1‐aryl‐2‐(arylthio)ethanones and 1‐alkyl‐2‐(alkylthio)ethanones with aryl/alkyl azides is reported as an efficient and general catalytic intermolecular procedure for the regiospecific synthesis of medicinally important 1, 5‐disubstituted 4‐arylthio‐ and 4‐alkylthio‐1, 2, 3‐triazoles and 1, 5‐disubstituted 1, 2, 3‐triazoles (see scheme; DBU=1, 8‐diazabicyclo[5.4.0]undec‐7‐ene).